REPRESENTAMEN OF MORALITIES ON LANGUAGE AND VISUAL SIGNS IN INCREDIBLES 2 FILM - Diyanto, Assyafa Puteri; Nurulaen, Yuyun; Rusmana, Dadan (Universitas Islam Negeri Sunan Gunung Djati, 2023)
Film stands out as a compelling contemporary mass medium that has witnessed substantial growth. This progress has given rise to numerous film genres, intended to captivate audiences across generations, including the realm of animated cinema. Often, films convey messages depicting the dichotomy between good and bad characters in everyday life, typically portraying the vulnerable and kind-hearted individuals facing oppression from self-centered antagonists. However, in fictional works like